2020
DOI: 10.1039/d0ra06871c
|View full text |Cite
|
Sign up to set email alerts
|

Tin(ii) chloride dihydrate/choline chloride deep eutectic solvent: redox properties in the fast synthesis of N-arylacetamides and indolo(pyrrolo)[1,2-a]quinoxalines

Abstract: Physicochemical and redox properties of SnCl2·2H2O/ChCl deep eutectic solvent were studied and applied in the synthesis of anilines, N-arylacetamides and indolo(pyrrolo)[1,2-a]quinoxalines starting from nitroaromatic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…However, bands below 900 cm –1 are associated with Sn–Cl bonds. These spectra are consistent with the previously published ones . However, at 3450 cm –1 , a broad vibrational band is observed that is attributed to O–H stretching.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, bands below 900 cm –1 are associated with Sn–Cl bonds. These spectra are consistent with the previously published ones . However, at 3450 cm –1 , a broad vibrational band is observed that is attributed to O–H stretching.…”
Section: Resultssupporting
confidence: 92%
“…These spectra are consistent with the previously published ones. 56 However, at 3450 cm −1 , a broad vibrational band is observed that is attributed to O−H stretching. This band broadens as the interaction between QAS ions weakens and chloride pledges new interactions with the metal salt dimers, designating the formation of electrostatic interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ochoa‐Puentes and co‐workers have revealed that a rapid reduction of 2‐( N ‐pyrrolyl)nitroarenes could be obtained in the presence of SnCl 2 ⋅ 2H 2 O/choline chloride (ChCl) eutectic mixture [20] . Such the simple tactic allowed for the annulation of aldehydes to afford C4‐substituted pyrrolo[1,2‐ a ]quinoxalines that featuring an array of functionalities (Scheme 21).…”
Section: Recent Methods For Synthesis Of Pyrrolo/indolo[12‐a]quinoxal...mentioning
confidence: 99%
“…Ochoa-Puentes and co-workers have revealed that a rapid reduction of 2-(N-pyrrolyl)nitroarenes could be obtained in the presence of SnCl 2 ⋅ 2H 2 O/choline chloride (ChCl) eutectic mixture. [20] Such the simple tactic allowed for the annulation of aldehydes to afford C4-substituted pyrrolo[1,2-a]quinoxalines that featuring an array of functionalities (Scheme 21). Although the mechanism has been still disputable at that moment, control experiments somewhat implied that the deep eutectic solvent only participated in the reduction, not the cyclization.…”
Section: Cyclization Of N-(2-nitroaryl)pyrroles/indolesmentioning
confidence: 99%
“…7, 133.5, 130.2, 128.5, 126.6, 125.5, 123.5, 123.0, 117.4, 101.8. 4-Bromoisoquinolin-1-amine (5d 7, 143.5, 135.1, 131.8, 127.0, 125.5, 125.1, 119.2, 104.9 4-Bromoaniline (5e). 24 Elution with 10:1 (v/v) mixed petroleum ether and ethyl acetate. Yield 40%, 20.5 mg; white solid; mp 62−63 °C; 1 H NMR (400 MHz, DMSO-d 6 ): δ 7.17 (d, J = 8.8 Hz, 2 H), 6.56 (d, J = 8.8 Hz, 2 H), 5.31 (s, 2 H); 13 C{ 1 H} NMR (100 MHz, DMSO-d 6 ): 148.5,131.8,116.2,.…”
mentioning
confidence: 99%